Democratic Decentralization and Participatory Development: Focus on Bangladesh - Pronita Dutta (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2020)
In recent decades, developing Asian nations have witnessed the emergence of democratic decentralized governance structures, and with it a shift towards a more people-centric approach to development. Proponents claim the new approach can humanize bureaucracies and provide solutions to problems of poverty and social inequity. Despite their popularity, difficulties in implementation have been found, and questions are now being asked about the ‘real’ effectiveness of such frameworks. Discussing first the tenets of participatory development and its symbiotic relationship with democratic decentralized on this paper looks at the challenges faced in decentralizing a decentralized participatory framework and the critical components needed for success. It draws on examples from within developing Asia to highlight the many complexities of the issue, such as different cultural beliefs, political forces, administrative arrangements and varying perceptions. It argues that where incorrectly implemented, a decentralized participatory structure can prove ineffective for local people, in some cases leading to practical disillusions and further disadvantage.